2020
DOI: 10.14198/jhse.2021.161.16
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and perceptions on doping among university students in physical education and sport science related degree programmes

Abstract: Doping cases have in the recent past (second decade of 21st century) tainted the Kenyan athletes' dominance in long distance running. The purpose of this study was to examine the knowledge, attitudes and perceptions (KAP) on doping among university students pursuing sport related courses. It was postulated that KAP on doping will be mediated by year of study, age, gender, sporting experience and degree programme. Data were collected through self-administered questionnaires from university students (n=179) draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 21 publications
(35 reference statements)
4
13
2
Order By: Relevance
“…0.0699 > 0.05, there is no difference in knowledge between male and female athletes. This is in line with Elijah et al (2021), who found no differences in knowledge, attitudes, or perceptions of doping between men and women [18]. There are significant differences in athletes' doping knowledge based on their educational degree.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…0.0699 > 0.05, there is no difference in knowledge between male and female athletes. This is in line with Elijah et al (2021), who found no differences in knowledge, attitudes, or perceptions of doping between men and women [18]. There are significant differences in athletes' doping knowledge based on their educational degree.…”
Section: Discussionsupporting
confidence: 90%
“…One of the things that influence knowledge is a person's level of education [19], [20]. Athletes with a lower degree of education have less doping knowledge than athletes with a higher level of education [18].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the study from Korea, this study did not show statistically significant differences in general attitudes toward PEDs usage between athletes playing individual and team sports [36]. Similar to study in Kenya, this study also did not show differences in athletes' general attitudes toward PEDs usage between young adults and adolescents [44]. Finally, this study established statistically significant difference in athletes' general attitudes toward PEDs regarding the length of sport engagement, where athletes who were engaged in sports for one to five years had more permissive attitudes toward PEDs usage in comparison with the athletes engaged in sports for six or more years.…”
Section: Discussioncontrasting
confidence: 65%
“…3 1 2 3 6 / o s f . i o / k 6 g y e | 19 to use performance enhancing substances" (Rintaugu & Mwangi, 2020). Because these items tap into a different aspect of doping attitude if any (general attitude vs. attitude about one's own doping related action) and because item level data were not presented to re-instate the 17item original scale, the study was excluded from meta-analysis.…”
Section: Performance-enhancement Attitude Scale Versionsmentioning
confidence: 99%